2016
DOI: 10.18410/jebmh/2016/244
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ocular Risk Factors for Primary Open-Angle Glaucoma

Abstract: Glaucoma causes irreversible progressive visual impairment. Increased intraocular pressure remains an important primary and prognostic risk factor for primary open-angle glaucoma (POAG), but its association with other risk factors is also present. This study was conducted to assess the relationship between potential ocular risk factors and the development of POAG to aid in early diagnosis. DESIGN Hospital based case control study. METHODS A case control study was conducted on 134 cases of POAG (Group 1) and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…In this study, 81 (36%) participants had HTN. This was comparable with a study done by Garg et al 21 where HTN was seen in 35.1% of their participants.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, 81 (36%) participants had HTN. This was comparable with a study done by Garg et al 21 where HTN was seen in 35.1% of their participants.…”
Section: Discussionsupporting
confidence: 91%
“…Diabetes cause microvascular damage and may affect vascular auto regulation of retina and optic nerve. 2 This maybe an added factor in our study, which showed higher incidence of glaucoma (12.4%) compared to general population. It maybe because the study was done in diabetic patients.…”
Section: Resultsmentioning
confidence: 56%
“…Among the 750 patients, 93 (12.4%) had glaucoma, which is high compared to other studies done in general population 2,6 (Table 4) (Figure 4). In our study, glaucoma was significantly more in diabetic patients with HT53 (15.2%) than patients without HT40 (10.0%) p value significant at 0.05 level (Table 5) ( Figure 5).…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations